Social and Philosophical Analysis of The Reforms In The New Uzbekistan Education System - Kudratullayevna, Akhmedova Dilafroz (Indonesian Journal Publisher, 2024)
This article analyzes the reforms implemented in the education system and the field of science in recent years, their results, and their practical applications. It provides a detailed discussion on the continuous improvement of the state education system and the proposal of innovative solutions to educational problems. Additionally, it discusses the significant attention given to education, science, and innovation in the “New Uzbekistan Development Strategy for 2022–2026” and the “Uzbekistan – 2030” strategies, which address several key issues in society and state life.